2017
DOI: 10.17116/otorino201782544-47
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of the combination of azelastine hydrochloride and mometasone furoate for the intranasal application in the patients presenting with seasonal allergic rhinitis

Abstract: The objective of the present work was to evaluate the effectiveness of the combination of azelastine hydrochloride and mometasone furoate for the intranasal application to treat the patients presenting with seasonal allergic rhinitis. A total of 60 subjects suffering from seasonal allergic rhinitis were available for the observation. All the patients were allocated to three groups comprised of 20 individuals each. The patients of the first group received the fixed combination of azelastine hydrochloride and mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…However, Du et al 33 analyzed the data from 5 studies and demonstrated that OAH/INCS combination therapy was more effective than INCS monotherapy for only rhinorrhea (95% CI, −0.07 to 0; I 2 = 0%; P for overall effect < 0.05), but not nasal congestion, sneezing, or itching. Of the 4 studies that used the RQLQ, 15 26 28 30 compared to INCS monotherapy, OAH/INCS combination therapy induced significant improvement in total mean scores of RQLQ (SMD, −0.26; 95% CI, −0.51 to −0.02; P = 0.04; I 2 = 78%); however, the difference did not exceed −0.50, which is the criterion for a clinically significant difference. 34 The change in the TOSS was reported in only one study, and there was no significant difference between combination therapy and monotherapy.…”
Section: Key Questions and Recommendationsmentioning
confidence: 98%
See 4 more Smart Citations
“…However, Du et al 33 analyzed the data from 5 studies and demonstrated that OAH/INCS combination therapy was more effective than INCS monotherapy for only rhinorrhea (95% CI, −0.07 to 0; I 2 = 0%; P for overall effect < 0.05), but not nasal congestion, sneezing, or itching. Of the 4 studies that used the RQLQ, 15 26 28 30 compared to INCS monotherapy, OAH/INCS combination therapy induced significant improvement in total mean scores of RQLQ (SMD, −0.26; 95% CI, −0.51 to −0.02; P = 0.04; I 2 = 78%); however, the difference did not exceed −0.50, which is the criterion for a clinically significant difference. 34 The change in the TOSS was reported in only one study, and there was no significant difference between combination therapy and monotherapy.…”
Section: Key Questions and Recommendationsmentioning
confidence: 98%
“… 12 14 24 Moreover, the RQLQ was described in 4 studies, and INCS/INAH combination therapy induced a more significant improvement over that of INCS monotherapy (MD, −0.24; 95% CI, −0.42 to −0.06; P = 0.009; I 2 = 79%). 11 12 14 15 24 In 3 studies, the TSS slightly decreased with the INCS/INAH combination therapy compared to INCS monotherapy, although this difference was not statistically significant (MD, −0.66; 95% CI, −2.02 to 0.71; P = 0.34; I 2 = 98%). 15 19 22 24 …”
Section: Key Questions and Recommendationsmentioning
confidence: 98%
See 3 more Smart Citations